A Necessary Evil? Patients' Experiences Receiving Tube Feeding in Acute Care. (August 2017) - Green, Cara; Vandall-Walker, Virginia
Background: Tube feeding (TF) is frequently prescribed for adults admitted to acute care facilities to prevent or ameliorate malnutrition, yet little is known about patients' needs and experiences with receiving this therapy. Patients' perspectives regarding the factors influencing their experiences, as well as their information and support needs, are required to inform healthcare providers' (HCPs') patient-centered practices. Methods: Based on an interpretive description qualitative approach, 12 unstructured face-to-face interviews were conducted with participants admitted to acute care hospitals in Northwestern Ontario, Canada. Results: Analysis of data revealed variations in participants' perceptions of the necessity for TF and the discomfort resulting from this therapy. Perceived necessity was influenced by interrelated themes: the meaning of TF (beyond necessity), the trust held in HCPs, and the resilience of participants in response to all that they were experiencing. Collectively, these findings are encompassed within the central theme, phrased as a question, about the experience of TF: "A necessary evil?" Participants' answers to this question revealed the nature of their overall response throughout TF therapy (ie, indifferent, resistant, relieved, or tolerant). Conclusions: The range of perceptions and the complexity of patients' experiences during TF revealed in the data can inform HCPs' patient-centered approaches to TF care. Assessing and incorporating patients' values, beliefs, needs, and goals into, and exploring their choices in, nutrition care planning can promote resilience in response to TF therapy. HCPs may then well enhance patients' comfort and overall experience with TF therapy.